Sanity, Madness, Transformation : The Psyche in Romanticism - Woodman, Ross Greig (Book collections on Project MUSE., 2005)
"In Sanity, Madness, Transformation, Ross Woodman offers an extended reflection on the relationship between sanity and madness in Romantic literature. Woodman is one of the field's most distinguished authorities on psychoanalysis and romanticism. Engaging with the works of Northrop Frye, Jacques Derrida, Sigmund Freud, and Carl Jung, he argues that madness is essential to the writings of William Blake, William Wordsworth, and Percy Shelley, and that it has been likewise fundamental to the emergence of the modern subject in psychoanalysis and literary theory. For Frye, madness threatens humanism, whereas for Derrida its relationship is more complex, and more productive. Both approaches are informed by Freudian and Jungian responses to the psyche, which, in turn, are drawn from an earlier Romantic ambivalence about madness." "This work, which began as a collection of Woodman's essays assembled by colleague Joel Faflak, quickly evolved into a new book of original compositions that approach Romanticism from a unique analytic perspective by returning madness to its proper place in the creative psyche. Sanity, Madness, Transformation is a provocative hybrid of theory, literary criticism, and autobiography and is yet another decisive step in a distinguished academic career."--Jacket.